Northern Badia teachers’ attitudes towards learning during the Corona pandemic - Al-Shurafat, Mashor Saker Mfadi (Journal of Educational and Psychological Sciences, 2022)
This study aimed to know the attitudes of teachers in the Directorate of Education in the North Eastern Badia region towards distance learning, and to achieve the goal of the study, the researcher used the descriptive analytical method. The study tool was a questionnaire that was applied to a random sample of (151) male and female teachers. The results of the study showed that the trends of teachers’ approval degree came with a degree of approval (neutral) with an arithmetic mean (3.47 out of 5) and a percentage (69.4%). The results did not show statistically significant differences in the attitudes of the teachers of the northeastern Badia towards distance learning due to the variable of gender or experience. In light of the results, the researcher presented a set of recommendations and proposals, the most important of which are: providing the appropriate infrastructure for digital transformation in terms of equipment, software and platforms, training teachers more on e- learning and distance learning, and developing distance learning platforms to be more effective and interactive between teacher and student.